PERANAN MASYARAKAT TERHADAP PENTINGNYA PENDIDIKAN ANAK USIA DINI UNTUK MENCETAK GENERASI UNGGUL di DUSUN PENANGAN DESA SOKAAN - Halima; Ivonne Hafidlatil Kiromi (UNZAH Genggong, 2020)
This study aims to examine the level of public awareness about the importance of education that children should get from an early age, because around us there are still many people who think that early childhood education is not important, such as in Dusun Penangan, Desa Sokaan. This study uses qualitative research with a descriptive approach, which is based on a natural background as a direct source of data, and researchers in this case as a research instrument, who are tasked with planning, executing, collecting data, analyzing, interpreting data and ultimately reporting the results of the research. The subjects of this study were 17 people in Penanga Sokaan Hamlet as the research sample. From the results of observations made by researchers, it is clear that the level of public awareness of the importance of education, especially in early childhood education is still very low, the surrounding community tends to underestimate education. Key words: the role of society, the superior generation